Empire of the air [videorecording (DVD)] : the men who made radio - Burns, Ken, 1953-; Robards, Jason; Lewis, Tom, 1942- (Ken Burns' America collection, 2004)
Story of radio from 1906-1955 and the three men who made it happen: Lee de Forest, Edwin Howard Armstrong, and David Sarnoff. Combines archival photographs, newsreels of the period, interviews, and radio soundtrack.